57PMultidisciplinary brain metastasis clinic: Is it effective and worthwhile?. (24th November 2019) - Rajpurohit, A; Patil, V M; Noronha, V; Joshi, A; Menon, N; Puranik, A; Purandare, N; Mahajan, A; Mummudi, N; Krishnatry, R; Kumar, R; Yadav, S; et al.
Abstract: Background: Management of brain metastasis is a complex multidisciplinary venture. Hence, we started a multidisciplinary brain metastasis clinic for opinion on difficult brain metastasis cases. This is the review of the impact of this clinic on the treatment decisions. Methods: Brain metastasis clinic (BMC) was started in the month of April 2018 and meets once a week. Data of patients discussed between 27th April 2018 to 28th June 2019 were included for thisanalysis. Treatment decision made by clinicians (before sending the patient to the BMC were compared with the decisions made in BMC. The decisions were broken on a predefined proforma as intent of treatment (curative or palliative), modalities planned (surgery, radiation, chemotherapy), type of therapy planned (details of each therapy) in each modality were collected both pre and post BMC. In addition, compliance of the respective physicians to BMC decision was also calculated. SPSS version 20 was used for analysis. Descriptive statistics was performed. Results: Ninety-nine patients were discussed in this time period. The median age was 51 (range 17-68) years. The gender distribution was 70 males (70.7%) and 29 females (29.3%). Lung was thepredominant site of malignancy (79, 79.8%). Thirty-one patients (31.3%) had EGFR TKI domain activating mutation while 17 (17.2%) had ALK rearrangement. The treatment plan was changed in 46 patients (46.5%). The intent of treatment was changed in 5 patients (5.3%). Change in treatment plan with respect to surgery in 9 patients (9.1%), radiation in 37 patients (37.4%), chemotherapy in 15 patients (15.2%), targeted therapy in 11 patients (22.9%) and intrathecal in 6 patients (6.1%) respectively. The compliance to the BMC decision in patients in whom it was changed was 84.8% (39, n = 46). Conclusions: Multidisciplinary management of difficult brain metastasis cases in specialized clinics has significant impact on treatment decisions. Legal entity responsible for the study: Tata Memorial Hospital, Mumbai. Funding: Has not received any funding. Disclosure: All authors have declared no conflicts of interest.